HIF-1α at the intersection of hypoxia, ferroptosis-associated stress, and cell death crosstalk in osteomyelitis - Li, Jinglin; Yang, Fuyin; Deng, Xuan; Yu, Yang; Huang, Xianpeng; Yang, Xuxu; Yang, Lidan; Zhang, Tao; Xiong, Huazhang (Frontiers in Cell and Developmental Biology, 2026)
Osteomyelitis is a severe inflammatory disease of bone tissue primarily caused by bacterial infections, most commonly Staphylococcus aureus. Its complex pathophysiology creates a unique hypoxic and inflamed microenvironment, which leads to the significant upregulation of the key transcriptional regulator, hypoxia-inducible factor-1α (HIF-1α). HIF-1α plays a pivotal role in disease progression, partly by orchestrating various forms of regulated cell death (RCD). The dysregulation of these RCD pathways, including apoptosis, pyroptosis, and particularly the emerging role of ferroptosis, is critically involved in shaping the fate of bone and immune cells, influencing the inflammatory response, and ultimately driving bone destruction. This review aims to comprehensively explore the regulatory mechanisms of HIF-1α on these RCD modalities, especially ferroptosis, and the intricate crosstalk among them. Moreover, we highlight emerging therapeutic strategies targeting the HIF-1α-RCD axis, offering novel insights into the pathogenesis and potential treatment avenues for this refractory orthopedic inflammatory condition.